2020
DOI: 10.1155/2020/4951591
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Electroacupuncture on Chronic Inflammatory Pain and Depression Comorbidity in Mice

Abstract: Comorbidity of chronic pain and major depression disorder (MDD) are common diseases. However, the mechanisms of electroacupuncture (EA) and the responses of N-methyl-D-aspartate receptors in the brain remain unclear. Three injections of complete Freund's adjuvant (CFA) were administered to induce chronic inflammatory pain (CIP). EA was then performed once every other day from days 14 to 28. Behavior tests of chronic pain and depression were evaluated to make sure of the successful induction of comorbidity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In addition, Nav1.8 is associated with signaling in nociceptive sensory afferents, and hyper function of this receptor is coordinated with hyperalgesia [ 64 ]. Both of these receptors have displayed involvement in nociceptive responses associated with TRPV1 involvement, and they concurrently display positive tendencies in the treatment of EA for conditions of chronic pain and depression [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nav1.8 is associated with signaling in nociceptive sensory afferents, and hyper function of this receptor is coordinated with hyperalgesia [ 64 ]. Both of these receptors have displayed involvement in nociceptive responses associated with TRPV1 involvement, and they concurrently display positive tendencies in the treatment of EA for conditions of chronic pain and depression [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus, prefrontal cortex, hypothalamus, olfactory bulb, striatum, and cerebellum were reported as susceptible brain areas under depression, and these regions were not only involved in the mechanism of depression but the antidepressant treatment (Huang et al., 2020; Xu et al., 2020; Yuan et al., 2020; Zhang et al., 2020). To some extent, the complex pathogenesis of depression may be a result of a disturbance of the network connection function of brain region.…”
Section: Introductionmentioning
confidence: 99%
“…Modern research has shown that acupuncture analgesia is related to the interaction of a variety of biologically active molecules in the pain process, including neurotransmitters, inflammatory mediators, cell signaling molecules and neuropeptides, etc. [ 39 41 ]. At the same time, relevant depression research also affirmed the antidepressant effects of acupuncture [ 42 ].…”
Section: Discussionmentioning
confidence: 99%